Advertising Education in Japan: Challenges in the Age of Globalization. (November 2019) - Morimoto, Mariko
The purpose of this commentary is to: illustrate the challenges that Japanese advertising education faces; find the possible causes for the difficulties faced; and consider potential solutions to overcome the challenges and prepare students for a fast-paced global workforce.